Digital Leadership and Innovation Management Toward nnovation Performance at Telkom Indonesia - Satya Nastiti, Arifiana; Wahyuningtyas, Ratri (Publisher Cv. Inara, 2026)
This study aims to examine the influence of digital leadership and innovation management on innovation performance in organizations. The research used a quantitative approach, with 100 respondents, and collected data via structured questionnaires. The analysis was performed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to evaluate the relationships among the variables. The results indicate that both digital leadership and innovation management have a significant and positive impact on innovation performance. Digital leadership enables leaders to utilize technology, foster an adaptive and innovative organizational culture, and support creative problem-solving. At the same time, effective innovation management ensures structured, collaborative, and responsive processes for idea generation, development, and implementation. Based on these findings, organizations are recommended to strengthen digital leadership capabilities and implement systematic innovation management practices to enhance innovation performance and sustain competitive advantage. These measures are crucial for organizations to respond effectively to environmental changes and achieve long-term growth.